Treatment Outcomes and Prognostic Factors of Pulmonary Metastasectomy for Bone and Soft Tissue Sarcoma: a High Volume Academic Institution Experience - Kang, Xiaozheng; Yan, Wanpu; Yang, Yongbo; Dai, Liang; Liang, Zhen; Huang, Zhen; Niu, Xiaohui; Chen, Keneng (Zhongguo fei ai za zhi, 2016)
The bone and soft tissue sarcoma can metastasize to distant sites, most commonly the lungs. Some cases can be cured by radical metastasectomy, but its role, indication and prognostic factors remains controversial. The rarity of the disease combined with the diverse number of subtypes can make bone and soft tissue sarcomas very difficult to study. There are few randomized control studies or international high volume results, and such reports in China are seldom seen. The aim of this study is to investigate surgical treatment outcomes and prognostic factors of pulmonary metastatic bone and soft tissue sarcoma patients. From January 2007 to December 2015, patients with bone and soft tissue sarcoma who underwent multimodality therapy including definitive surgery for the primary lesion and at least one pulmonary metastasectomy were enrolled in the retrospective study. All the relevant clinical variables were collected, and then statistically analyzed and interpreted with the aid of univariate and multivariate Cox